Determinan Sikap Etika Mahasiswa Akuntansi (Studi Kasus pada Mahasiswa Akuntansi di Kota Malang) - Lestari, Ida Ayu; Diana, Nur; Nandiroh, Umi (Universitas Islam Malang, 2024)
This research aims to analyze the influence of intellectual intelligence, spiritual intelligence, and locus of control on students' ethical attitudes. This research is quantitative research with characteristics of correlational research using primary data obtained from questionnaires and measured using a Likert Scale. The data analysis method used is multiple linear regression analysis which is processed using SPSS software. The population in this study were Accounting Students Class of 2020 in Malang City from the Islamic University of Malang, State University of Malang, State Polytechnic of Malang, and State Islamic University of Maulana Malik Ibrahim Malang. Data was collected from 100 respondents through a questionnaire given to Bachelor of Accounting students class of 2020 in Malang City, using a purposive sampling technique. The results of the analysis show that simultaneously intellectual intelligence, spiritual intelligence and locus of control have an effect on students' ethical attitudes, partially spiritual intelligence and locus of control have a significant positive effect on students' ethical attitudes, while intellectual intelligence has no effect on students' ethical attitudes.Keywords: Intellectual intelligence, spiritual intelligence, locus of control, students' ethical attitudes